Efektivitas Distribusi Subsidi Pupuk Organik dan Dampaknya terhadap Pendapatan Usahatani Padi Sawah di Subak Sungsang, Desa Tibubiu, Kabupaten Tabanan - ARISANDI, NI WAYAN WINDA; SUDARMA, I MADE; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Effectivity of Subsidized Organic Fertilizer and its Impact toward Rice Farmer’s Income at Subak Sungsang, Tibubiu Village, Tabanan Regency Balinese Government has established a subsidized solid organic fertilizer policy produced by the Integrated Farming System (Simantri), group of farmer who maintain the organic fertilizer processing machine (APPO) and Organic Fertilizer Producing Training House (RPPO). The policy of organic fertilizer subsidy has been established since 2013. Subak Sungsang is one of many villages who receive subsidized organic fertilizer since 2014 and still using balanced compound fertilizer to its rice farm.The purpose of this research is to know the effectivity of subsidized organic fertilizer distribution and the impact of using balanced compound fertilizer toward rice farmer’s income at Subak Sungsang. The method that is used to measure the effectivity of subsidized organic fertilizer distribution is through “four proper” in which are proper of price, proper of place, proper of time and proper of amount and income analysis to know the comparison of balanced compound fertilizer’s income and full capacity of chemical fertilizer’s income. The result of this research shows that the distribution of subsidized organic fertilizer in terms of proper of price, place, and time is very effective (100%), while in term of proper of amount is very ineffective (0%). Based on the analysis of rice farm’s income, the average income of the Subak Sungsang respondents is increasing from Rp. 6.704.185,82/crop season by using full capacity of chemical fertilizer to Rp. 8.932.832,73/crop season by using balanced compound fertilizer. Keywords: Distribution Effectivity, Organic Fertilizer Subsidy, Rice Farmer’s Income